Factors and moderating effect of internet self-efficacy on Malaysia MOOCs continuance intention for higher education - Mawaddah, Mohamad (2018)
MOOCs continuance intention is an open question as the completion rates and the overall use of the system were substantially low. Consequently, there have been extensive efforts to understand the phenomena. Yet, documented findings regarding the determinant of the continuous use of MOOCs are not all together consistent. To provide more insight, this study developed a research model consisting of four contributing factors related to MOOCs features, namely usefulness, enjoyment, interactivity and openness in order to understand how these factors affect MOOCs continuance intention at the higher education level in Malaysia. In addition, Internet self-efficacy was proposed as a moderator variable to give a better understanding of how the individual difference affects continuance intention. Using the quantitative approach, online questionnaires were distributed to students enrolled in Malaysia MOOCs program, registered in OpenLearning platform. A total of 267 valid questionnaires were used for the analysis using the Partial Least Square Path Model (PLSPM) approach. The findings revealed that continuance intention was directly affected by usefulness, enjoyment and openness, but not interactivity. Perhaps the tasks given in the MOOCs activities were more related to the individual assignment which does not trigger students to interact, causing them to feel less connected in the MOOCs environment. Then the analysis was run to test the moderating effect of Internet self-efficacy. The results indicated that Internet self-efficacy negatively moderated the relationship between usefulness, enjoyment, and interactivity on continuance intention respectively. This tendency implies that users at the lower end of the moderating effect tend to place more effort in achieving better continuance intention than those at the upper end. Overall, this study enriches the literature by providing evidence of the importance of MOOCs features in improving continuance intention and finally highlights the moderating effect of Internet self-efficacy on the relationship between MOOCs features and continuance intention.